2021
DOI: 10.3390/su13084293
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the Nonsubsidized Consumption Promotion Mechanisms of New Energy Vehicles to Potential Consumers’ Purchase Intention

Abstract: With the background of China’s new energy vehicles (NEVs) subsidies declining, there is an important practical significance to effectively play the role of the nonsubsidized consumption promotion mechanisms. The nonsubsidized mechanisms for NEVs are classified into two types—concept induction and policy incentives, and differences in the sensitivity of the two types of mechanisms on potential consumer purchase intentions due to differences in urban traffic patterns and consumer education levels are analyzed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Zhao et al (2022) discovered that personal norms and green self-identity are positively correlated with purchase intention. Li and Guo (2022), Li et al (2021), Sun and Xu (2018), , and other scholars have conducted detailed studies on different types of consumers' consumption preferences from multiple perspectives.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zhao et al (2022) discovered that personal norms and green self-identity are positively correlated with purchase intention. Li and Guo (2022), Li et al (2021), Sun and Xu (2018), , and other scholars have conducted detailed studies on different types of consumers' consumption preferences from multiple perspectives.…”
Section: Literature Reviewmentioning
confidence: 99%
“…, 2021). The effective implementation of subsidy policies needs to be tailored to local conditions (Liu and Yi, 2020; Lin et al. , 2021) while also considering consumer characteristics (Xiong and Wang, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In terms of policy feasibility, some scholars have found that subsidy policies can effectively promote new EVs, play a role in low carbon emission reduction and improve air quality (Xie et al, 2021;Wang et al, 2021;Zhang et al, 2020;Yin and Liu, 2021;Zhao et al, 2021). The effective implementation of subsidy policies needs to be tailored to local conditions (Liu and Yi, 2020;Lin et al, 2021) while also considering consumer characteristics (Xiong and Wang, 2020). In terms of policy comparison, scholars conduct comparative studies on the existing policies of EVs, including tax cuts, subsidies and price discount policies (Yang and Tang, 2019;Yin et al, 2020;Shao et al, 2017;Zhu et al, 2021).…”
Section: Research On the Policy Factorsmentioning
confidence: 99%
“…The research of domestic and foreign scholars on the development of the new energy vehicle industry mainly focuses on policy promotion, influencing factors, etc. Regarding policy promotion, Chakraborty [ 3 ] and Jiao [ 4 ] conducted research from the perspective of "subsidized" policy tools, and Lin [ 5 ] studied the impact of "non-subsidy" policies on the promotion of new energy vehicles. Sun [ 6 ] and Jiang [ 7 ] considered the advancement and diffusion of new energy vehicles from the consumer demand perspective.…”
Section: Introductionmentioning
confidence: 99%